Stabilitas Warna Resin Komposit Nanohibrida Setelah Perendaman Dalam Larutan Teh Dengan Berbagai Tingkat Oksidasi - Septina Anggun Putri; Rinda Yulianti; Maya Hudiyati (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Nano-hybrid composite is a resin-based composite that combines mini and Nano-sized fillers. It has excellent mechanical properties and polish ability, but susceptible to color change. The color change of resin composite can be influenced by colored drinks such as tea which have various oxidation levels which will affect composition of tea coloring agent. The aim of this study was to determine color stability of Nano-hybrid composite after immersion in tea solutions with various levels of oxidation. Thirty disc-shaped specimens with diameteri10imm and thickness 2 mm were made from Filtek Z250XT Nano-hybrid composite. Specimens were stored in water at 37°C for 24 hours and then divided randomly into five groups which were immersed in distilled water, white tea, green tea, oolong tea, and black tea. Each group was immersed at 37°C for 22 days. Color was assessed in the CIELAB color system using a colorimeter before and after immersion. Data were analyzed with one way ANOVA and LSD Post-hoc test. Color changes was occurred in all groups with ∆E* as 3.209 for distilled water, 7.841 for white tea, 4.111 for green tea, 6.917 for oolong tea, and 8.340 for black tea. Color change in white tea, oolong tea, and black tea was significantly higher than in distilled water and green tea, also in black tea than in oolong tea. There are significant differences in color stability of Nano-hybrid composites after immersion in tea solution with various oxidation level, and green tea promotes the lowest color change